Improved immunogenicity of individual influenza vaccine components delivered with a novel dissolving microneedle patch stable at room temperature - Vassilieva, Elena V. (Drug Deliv Transl Res, 2015)
Prevention of seasonal influenza epidemics and pandemics relies on widespread vaccination coverage to induce protective immunity. In addition to a good antigenic match with the circulating viruses, the effectiveness of individual strains represented in the trivalent vaccines depends on their immunogenicity. In this study we evaluated the immunogenicity of H1N1, H3N2 and B seasonal influenza virus vaccine strains delivered individually with a novel dissolving microneedle patch and the stability of this formulation during storage at 25°C. Our data demonstrate that all strains retained their antigenic activity after incorporation in the dissolving patches as measured by SRID assay and immune responses to vaccination in BALB/c mice. After a single immunization all three antigens delivered with microneedle patches induced superior neutralizing antibody titers compared to intramuscular immunization. Cutaneous antigen delivery was especially beneficial for the less immunogenic B strain. Mice immunized with dissolving microneedle patches encapsulating influenza A/Brisbane/59/07 (H1N1) vaccine were fully protected against lethal challenge by homologous mouse-adapted influenza virus. All vaccine components retained activity during storage at room temperature for at least three months as measured in vitro by SRID assay and in vivo by mouse immunization studies. Our data demonstrate that dissolving microneedle patches are a promising advance for influenza cutaneous vaccination due to improved immune responses using less immunogenic influenza antigens and enhanced stability.